Tingkat Efisiensi Dan Total Produktivitas Bank Umum Syariah Di Indonesia Tahun 2010-2014 Menggunakan Pendekatan Dea Dan Malmquist Index - Pontoh, Sasmita Claudia (Arthavidya Jurnal Ilmiah Ekonomi, 2016)
ABSTRACT. The aim of this research is to analyze the efficiency andtotal productivity of Islamic banks in Indonesia from 2010-2014 usingDEA method and Malmquist Index method. Results of this researchindicate that efficiency growth of Islamic banks in Indonesia from2010-2014 with Data Envelopment Analysis method is increasedand total productivity growth of Islamic banks in Indonesia from2010-2014 with Malmquist Index method is increased. From 11Islamic banks in Indonesia that selected as research sample, BankMuamalat Indonesia had the highest performance of efficiency andtotal productivity from 2010-2014.